Sudan : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This selected issues paper on Sudan was prepared by a staff team of the International Monetary Fund as background documentation for the periodic consultation with the member country. It is based on the information available at the time it was completed on September 7, 2012. The views expressed in this document are those of the staff team and do not necessarily reflect the views of the government of Sudan or the Executive Board of the IMF.